An Application of Blended Palm Oil Waste in Brick Production - Jusli, Euniza; Ling, Jen Hua; Bujang, Mastura; Ali, Dayang Siti Hazimmah; Lee, Toh Sing (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2021)
Cement brick is an essential construction component, which uses cement as the primary binder. The cement industry was identified as the major contributor to carbon dioxide emission, which is a greenhouse gas. The application of agro-industrial waste as partial cement replacement can reduce the negative impacts on the environment. In this study, the palm oil wastes, namely Palm Oil Clinker Powder (POCP) and Palm Oil Boiler Ash (POBA), were used as partial cement replacement. A total of 60 specimens were prepared with 0%, 10%, 20%, and 30% cement replacement by POCP and POBA. The physical and mechanical properties of bricks, such as density, water absorption, voids, and compressive strength, were investigated. The results show that the brick with 20% CP and BA could be used as a severe weathering brick.